Catalase and Glutathione Peroxidase in Dogs Naturally Infected by Leishmania infantum - Lopes-Neto, Belarmino Eugênio; Santos, Glauco Jonas Lemos; Lima, Adam Leal; Barbosa, Maritza Cavalcante; Santos, Talya Ellen Jesus dos; Uchoa, Daniel Couto; Pinheiro, Ana Débora Nunes; Pinheiro, Romélia Gonçalvez; Nunes-Pinheiro, Diana Célia Sousa (Acta Scientiae Veterinariae, 2016)
Background: Canine leishmaniasis (CanL) is caused by an obligatory intracellular parasite of Leishmania genus that affects organs and tissues. Several studies evaluate the role of reactive oxygen species (ROS) in the pathogenesis of many diseases. The overproduction of ROS on infectious diseases can induce an imbalance between oxidants and antioxidants at cellular or systemic level. Thus, the aim of this study was to evaluate the activity of antioxidant enzymes in CanL. Materials, Methods & Results: Females (n = 17) and males (n = 10), at different ages and with different weight, were selected for this study. Dogs were divided into two groups according classical clinical signs and sorological test to CanL. Animals were considered infected based on indirect immunofluorescent assay and ELISA titration ≥ 1:40. Group B (n = 15) composed by positive dogs to CanL from Zoonosis Control Center of Fortaleza (Ceará, Brazil) and group A (n = 12) was composed by dogs from private kennel that were serologically negative to L. infantum and had absence of clinical signs to CanL. Blood sample were collected for evaluation of hematological and biochemical parameters and glutathione peroxidase (GPx) and catalase (CAT) enzymatic activity. Data were analyzed by Student’s t-test and Pearson correlation coefficient (P < 0.05). Total proteins (TP, mg/dL) and alkaline phosphatase (ALP, U/L) were increased (P < 0.05) on group B (8.2 ± 1.2; 165.4 ± 46.4) when compared to group A (6.5 ± 1.1; 109.1 ± 38.3), respectively. Hemoglobin (Hb; g/dL) and hematocrit (Hct; %) were decreased (P < 0.05) on Group B (14.7 ± 1.8; 48.2 ± 5.7) when compared to group A (16.5 ± 1.3; 52.1 ± 2.4), respectively. Group B presented CAT (U/g Hb) and GPx (mU/mg Hb) lower (189.4 ± 90.4; 3,609.6 ± 1,569.1) than group A (326.6 ± 104.5; 5,055.6 ±1,569.1), respectively (P < 0.001). Positive correlation was observed between RBC and CAT; however, it was not significant. Discussion: Organisms require a good defense system in order to revert the overproduction of free radicals and consequently the injuries caused by them. This is possible through the production of antioxidant agents, which act on oxidative prevention and on tissue and cellular regeneration, by taking the reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) enzymes in the frontline. Erythrocyte changes promoted by CanL suggest possible correlation between anemia and the appearance of clinical signs, which in many cases is not seen. Erythrocytes contain SOD, CAT and GPx enzymes, thus, changes in these cells will reflect on the activity of these enzymes. In our results only CAT showed positive correlation with erythrocyte count, however it was not significant. GPx activity was lower (P < 0.001) in infected dogs than control group. This result agrees with another study, which showed a decrease in GPx levels in CanL, although it was not significant. However, it was found a positive correlation (P < 0.001) between erythrocytes and GPx activity and between hemoglobin and GPx activity in animals with leishmaniasis. These results suggest that the reduction in detoxification activity can be related to the decrease in erythrocyte count and that the GPx activity depends on the control mechanism of the antioxidant system in CanL. Furthermore, this result could be associated with decrease of blood cell count in animals with CanL, once GPx is an erythrocyte enzyme, which plays an important role in hemoglobin protection against oxidative damage. This study was carried out in naturally infected dogs with L. infantum. In conclusion, CAT and GPx activities are relate to oxidative stress induced by L. infantum infection and can be used as biomarkers on CanL.